Tolerability and efficacy of duloxetine for the prevention of persistent musculoskeletal pain after trauma and injury: a pilot three-group randomized controlled trial. Issue 4 (15th April 2023) - Beaudoin, Francesca L.; Gaither, Rachel; DeLomba, Weston C.; McLean, Samuel A.
Abstract : A randomized, double-blind, placebo-controlled clinical trial of duloxetine shows promise for the prevention of persistent posttraumatic pain when initiated in the acute period of injury. Abstract: This study investigated the tolerability and preliminary efficacy of duloxetine as an alternative nonopioid therapeutic option for the prevention of persistent musculoskeletal pain (MSP) among adults presenting to the emergency department with acute MSP after trauma or injury. In this randomized, double-blind, placebo-controlled study, eligible participants (n = 78) were randomized to 2 weeks of a daily dose of one of the following: placebo (n = 27), 30 mg duloxetine (n = 24), or 60 mg duloxetine (n = 27). Tolerability, the primary outcome, was measured by dropout rate and adverse effects. Secondary outcomes assessed drug efficacy as measured by (1) the proportion of participants with moderate to severe pain (numerical rating scale ≥ 4) at 6 weeks (pain persistence); and (2) average pain by group over the six-week study period. We also explored treatment effects by type of trauma (motor vehicle collision [MVC] vs non-MVC). In both intervention groups, duloxetine was well tolerated and there were no serious adverse events. There was a statistically significant difference in pain over time for the 60 mg vs placebo group ( P = 0.03) but not for the 30 mg vs placebo group ( P = 0.51). In both types of analyses, the size of the effect of duloxetine was larger in MVC vs non-MVC injury. Consistent with the role of stress systems in the development of chronic pain after traumatic stress, our data indicate duloxetine may be a treatment option for reducing the transition from acute to persistent MSP. Larger randomized controlled trials are needed to confirm these promising results.